The Essence of Classroom Technique and Activities in Teaching Listening as A Foundation Skill for Other Skills in The Early Acquisition of Language - Kurniawati, Dewi (English Education: Jurnal Tadris Bahasa Inggris, 2016)
This article discusses teaching and learning Listening English, especially teaching and learning Listening to children which play an important role on language acquisition.  Listening is always referred to as a boring lesson. Most of students are always feel trouble before trying Listening lessons. This is a challenge for us as English teacher. Here we must make the class become more interactive. Listening is the basis for the development of all other skills and the main channel through which the student makes initial contact with the target language and its culture. On the Interactive class, students not only listen, filling in the blanks, and answer questions, but they also discuss, dialogue, debate in conversation with each other and teachers can also incorporate the game in that classroom learning more fun and interactive. Everyone can participate in the class of Listening in the sense that they can improve their skills in listening, grammar, pronunciation, vocabulary, and speaking. Teachers assess Listening through the application of appropriate assessment with learning Listening, such as how well they capture the information they hear from the voice or video then they can discuss it together with each other in the classroom (could play, debates, discussions, etc.).